2021
DOI: 10.21203/rs.3.rs-248237/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Timing, Distribution and Predictors of Mortality Following a Road Traffic Injury in Northwest Ethiopia: A Hospital-Based Prospective Follow up Study

Abstract: BackgroundRoad traffic injury-related mortality continues to increase from time to time globally, but its burden is more than three times higher in low-income countries. This discrepancy is mainly due to poor trauma care system both at the pre-hospital and in-hospital. The analysis of injury patterns and time to mortality is crucial for the development and improvement of trauma care systems. This study aimed to identify patterns of RTI , and predictors of mortality following a RTI. MethodsA prospective hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
2
2
1
Order By: Relevance
“…Low systolic blood pressure at admission was a significant predictor for mortality among road traffic accident victims in our study. This finding is in agreement with previous studies that confirmed victims with low systolic blood pressure were at increased risk of death, which might be due to acute blood loss [12,21,26,36]. Poor blood perfusion to the vital organs due to low systolic blood pressure leads to a decompensation state with multiple organ failure and could increase mortality among road traffic accident victims [37].…”
Section: Plos Onesupporting
confidence: 93%
See 4 more Smart Citations
“…Low systolic blood pressure at admission was a significant predictor for mortality among road traffic accident victims in our study. This finding is in agreement with previous studies that confirmed victims with low systolic blood pressure were at increased risk of death, which might be due to acute blood loss [12,21,26,36]. Poor blood perfusion to the vital organs due to low systolic blood pressure leads to a decompensation state with multiple organ failure and could increase mortality among road traffic accident victims [37].…”
Section: Plos Onesupporting
confidence: 93%
“…; those victims who had a low GCS value were at a higher risk of death than those who had a high GCS value at admission [22,31,36]. And also in our studies, victims with severe head injuries (GCS�8) had the highest incidence of mortality, which is in line with other studies conducted in Ethiopia [12,38].…”
Section: Plos Onesupporting
confidence: 91%
See 3 more Smart Citations